Developing a core outcome set for interventions in people with mild cognitive impairment: study protocol - Angus G K McNair; Nicholas Turner; Alan Richardson; Elizabeth Coulthard; Jemima Dooley; Julie Clayton; Sam Harding; Sarah Rudd; Victoria Grace Gabb; Winsome Barrett-Muir; Natalie Woodward; Sophie Alderman; et al. (BMJ Open)
Introduction There is no standardised national guidance on clinical management for people living with mild cognitive impairment (MCI), and therapeutic interventions are limited. Understanding what outcomes are important and meaningful to people living with MCI and developing a core outcome set (COS) for research and clinical practice will improve the impact of clinical research and contribute towards developing effective care pathways for MCI. This study aims to develop a COS for adults living with MCI intended for use in interventional and clinical settings.Methods and analysis The COS will be developed using a five-stage study design: (1) systematic literature search, (2) qualitative interviews, (3) evidence synthesis from stages 1 and 2, (4) two-round Delphi survey and (5) consensus meeting(s). First, we will conduct an umbrella review of existing MCI interventional studies and extract a list of outcomes. Qualitative interviews will be held with key stakeholders including individuals living with MCI, friends and family, and relevant professionals to identify further outcomes considered important. Outcomes from the review and interviews will be synthesised into a ‘long list’ of outcomes for potential inclusion in the COS. Two rounds of Delphi surveys followed by a consensus meeting will be used to reach stakeholder consensus on which outcomes should be included in the final COS.Ethics and dissemination We have received ethical approval from the London—Queen Square Research Ethics Committee (23/PR/1580). Patient and public involvement and engagement are central to developing the COS. The results will be disseminated via conferences, peer-reviewed publications, briefing notes to key agencies, to the public via social media and blog posts and directly to stakeholders who participate in the project.Trial registration number Core Outcome Measures in Effectiveness Trials Initiative 2117; PROSPERO registration: CRD42023452514.